The Effect of Student Gender on the Obstetrics and Gynecology Clerkship Experience - Chang, Judy C. (Mary Ann Liebert, Inc., 2010)
OBJECTIVES: To explore the effects of the students' gender on their perception of quality and quantity of teaching, the amount of experiential learning, and their interest in obstetrics and gynecology. METHODS: Anonymous, self-administered surveys to third-year medical students rotating on the obstetrics and gynecology clerkship. RESULTS: Eighty-one of 91 students participated (89% response rate): 33 men, 46 women, 2 declined to reveal their gender. No significant gender differences existed regarding number of interactions with residents and faculty; number of deliveries, surgeries, or examinations performed; perceived quality of teaching; or feeling included as part of the clinical team. Male students were more likely to report performing specific surgical procedures, such as operating the bovie cautery during gynecological surgeries (p = 0.005). More men experienced patients refusing to allow them to participate in the clinical interview (p < 0.0001) and physical examination (p < 0.0001). Male students were also more likely to report feeling that their gender negatively impacted their clerkship experience (p < 0.0001). Although less likely to report preclerkship and postclerkship career interest in obstetrics and gynecology, male students were more likely to report that their interest increased at the end of the clerkship. CONCLUSIONS: Male students were more likely to experience gender bias from patients on the obstetrics and gynecology service. Male students also described feeling socially excluded from female-dominated clinical teams. Obstetrics and gynecology educators need to consider methods of encouraging patients to accept medical student participation regardless of gender. Obstetrics and gynecology faculty and residents need to be sensitive to subtle forms of gender bias and ensure equal inclusion for both male and female medical students.